Field survey for some fungal diseases on egg plant - Mishra, A K; Mishra, Mishra Kumar (International Multidisciplinary Research Journal, 2012)
India is the second largest producer of vegetables next only to china. The prime need of our nation is to improve the vegetables as most of the population of INDIA is vegetarian. In this country, Eggplant is important crop due to its cheaper rate and easy availability. Several diseases pose a great threat to the cultivation of eggplant. These diseases not only reduce the yield of fruits but also deteriorate the quality of fruits.